Transport properties and anisotropy of superconducting (Li1−xFex)OHFeSe single crystals. (29th March 2016) - Wang, Chunlei; Yi, Xiaolei; Qiu, Yang; Tang, Qingbin; Zhang, Xinwei; Luo, Yongsong; Yu, Benhai
Abstract: Large size single crystals of (Li1− x Fe x )OHFeSe have been synthesized via a hydrothermal ion-exchange technique using K0.8 Fe2 Se2 single crystals as the main raw material. The onset superconducting transition temperature is up to 40.3 K. The critical current density is as large as 1.9 × 10 5 A cm −2 at 5 K and self field. The upper critical fields have been determined by analyzing the relationship between resistivity and temperature under different applied fields along c -axis and ab -plane, respectively. An anisotropic factor about 11 is obtained, which is further confirmed by fitting the data obtained from the angle-dependent resistivity according to the anisotropic Ginzburg–Landau theory. The flux pinning potential ( U 0 / k B ) is as large as 6429 and 3115 K at 0.1 T in H // ab and H // c orientation, respectively. However, the flux pinning potentials are very sensitive to the applied magnetic field and will fast decrease with increase of the magnetic field in both directions, which are obviously different from the Ba1− x K x Fe2 As2 superconductor indicating a different flux pinning mechanism in the two kinds of superconductors.